CHARACTERISTICS OF PINE NEEDLES EXPOSED TO POLLUTION IN SILESIA, POLAND: CARBON ISOTOPES, iWUE, AND TRACE ELEMENT CONCENTRATIONS IN PINE NEEDLES. Issue 1 (2nd February 2023) - Sensuła, Barbara; Piotrowska, Natalia; Nowińska, Katarzyna; Koruszowic, Michał; Lazaj, Dawid; Osadnik, Rafał; Paluch, Radosław; Stasiak, Adam; Strączek, Beniamin
ABSTRACT: Here, we present the results of carbon isotope and elemental analysis of one-year-old Pinus Sylvestris L. needles collected in 2021 from 10 sampling sites in a highly populated and industrialized area of Poland. The needles were exposed to air pollution for one year. The chemical analysis of the samples was performed using different methods: radiocarbon analysis by accelerator mass spectrometry, stable isotope analysis using isotope ratio mass spectrometry, and elemental analysis by inductively coupled plasma-atomic emission spectroscopy. Variations in the carbon isotopes and elemental composition of pine needles were due to a mixture of carbon dioxide originating from different sources such as households, vehicle traffic, and industrial factories.